NEW ASPECTS OF SEPSIS AND SEPTIC SHOCK PATHOGENESIS IN CHILDREN. THE COMPLEMENT SYSTEM AS TARGET FOR AN EFFECTIVE THERAPY - A. P. Prodeus; M. V. Ustinova; A. A. Korsunskiy; A. G. Goncharov (Инфекция и иммунитет, 2018)
Nowadays sepsis is grave complication of infection end the cause of death reanimation. In this survey, we would like to emphasize the importance of the control over the activation over the compliment system. It has been proved of animal model a complement one of the key role in the development of hyperactive immunity response, later resulting in violation of immunity homeostasis. Mice which had C3–/–, C4–/– deficit, aft receiving a LPS dose intraperitoneallis showed a better survival to compare with the control group of animals. There exist clinical data which confirm active participation of the compliment in the chain of the septic process. The research showed the patient affected by sepsis, had protein C3 and C4 concentration correlating which mortality at the time of diagnosis. The is chemoattractants, protein C3a and C5a, turn tube the result of complements pathway activation. The chemoattractants, provoke the extraction a big number of cytokines. Vessels permeability increase and DIC-syndrome activation wis it, multiple organ dysfunction develops. Ishemiareperfusion launch triggers aseptic inflammation, which appears decentralization and DIC-syndrome. C1-INH controls the work of classical way complement and Hemostasis System. Researchers the deficit in C1-INH animals and patients affected bay sepsis, which is proved in laboratory and clinics. The remedy C1-INH (Berinert, CSL Behring) appeared over 25 years ago and was used and therapy hereditary angioedema. For the lasted years we accumulated a considerable quantity of fasts of C1-INH use which after pathologies: heart attack, Ischemia-reperfusion injury, trauma provoked by cardiopulmonary bypass. The use of C1-INH on animal models septic in clinical research their efficacy and safety.